The Management of Village Fund Finances - Meutia, Inten; Liliana, Liliana (Jurnal Dinamika Akuntansi, 2017)
The purpose of this research is to know the implementation of fund management of village fund in Ogan Ilir Regency, South Sumatera. The population in this study were 224 villages in Ogan Ilir Regency that received the allocation of Village Funds in 2016. The purposive sampling technique was applied to obtain samples and produce 26 villages. The analysis will be carried out with a quantitative and qualitative description process. Based on the data obtained, the researcher tries to describe or describe systematically, accurately, and factually about matters relating to the field as fact, nature, and relationship between phenomena. Quantitative techniques will also use frequency analysis that aims to provide an overview of the general condition. The results reveal that the financial management aspects are generally in accordance with those set out in Permendagri 113/2014 and have complied with the basic principles of financial management. Reporting and accountability remain a problem for some villages. Not all of the villages studied have aspects of human resource reporting and accountability. Taking into account the composition of village budgeting, the village does not meet the rules that require a ratio of 70:30, this results in inequality in the implementation of rural development. The conclusion of this research is that the implementation of village fund management in Ogan Ilur Regency has been running well according to Permendagri 113/2014.